HOW MASS MEDIA SHAPES PUBLIC OPINION (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores how mass media influences public opinion in modern society. It examines the ways in which television, newspapers, and especially social media shape people’s views on political, social, and cultural issues. The study highlights both the positive and negative effects of media, including its role in spreading information, raising awareness, and, at the same time, creating bias
Keywords: Mass media, Public opinion, Social media, Information, Influence, Communication, News, Media literacy, Misinformation, Bias, Society,Awareness